2017
DOI: 10.1007/s00592-017-1063-1
|View full text |Cite
|
Sign up to set email alerts
|

HLA, infections and inflammation in early stages of atherosclerosis in children with type 1 diabetes

Abstract: AimsThis prospective study focuses on risk factors for arterial damage in children with type 1 diabetes (T1D). MethodsEighty children and adolescents with T1D were investigated twice, approximately 2 years apart, for carotid artery intima-media thickness (cIMT) and compliance (CAC), flow-mediated dilatation (FMD) of the brachial artery, and plasma levels of matrix metalloproteinase (MMP)-8. All subjects were genotyped for HLA. The number of respiratory tract infections (RTI) during the past year was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Obesity and T2D are characterized by a state of systemic chronic low-grade inflammation, that triggers a vicious circle involving insulin resistance, oxidative stress and endothelial dysfunction and lays the basis for early and accelerated atherosclerosis [ 46 ]. A low-grade inflammation is also observed in lean children with T1D, while increased levels of pro-inflammatory cytokines are described, either in T1D or T2D [ 48 , 49 ]. Continuous systemic chronic inflammation from childhood accelerates plaque formation and contributes to its growth [ 48 ].…”
Section: Inflammation In Children and Adolescents With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and T2D are characterized by a state of systemic chronic low-grade inflammation, that triggers a vicious circle involving insulin resistance, oxidative stress and endothelial dysfunction and lays the basis for early and accelerated atherosclerosis [ 46 ]. A low-grade inflammation is also observed in lean children with T1D, while increased levels of pro-inflammatory cytokines are described, either in T1D or T2D [ 48 , 49 ]. Continuous systemic chronic inflammation from childhood accelerates plaque formation and contributes to its growth [ 48 ].…”
Section: Inflammation In Children and Adolescents With Diabetesmentioning
confidence: 99%
“…A low-grade inflammation is also observed in lean children with T1D, while increased levels of pro-inflammatory cytokines are described, either in T1D or T2D [ 48 , 49 ]. Continuous systemic chronic inflammation from childhood accelerates plaque formation and contributes to its growth [ 48 ]. Nearly 700 adolescents aged between 10 and 17 years who had a recent diagnosis of T2D were studied, and a detrimental inflammatory profile that worsened over time was shown [ 50 ].…”
Section: Inflammation In Children and Adolescents With Diabetesmentioning
confidence: 99%
“…In addition to HLA‐conferred disease risk, lifestyle and environmental factors (eg, in the form of early childhood respiratory infections) are associated with an increased risk for the development of islet autoimmunity and T1D. Diabetic children with the DQ2/DQ8 risk haplotype have been shown to have worse endothelial cell dysfunction and atherosclerotic changes in vasculature after acute respiratory infections than healthy children indicating interplay between HLA and infections on the wall of blood vessels . In addition, class I HLA genes have been associated with T1D.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…Diabetic children with the DQ2/DQ8 risk haplotype have been shown to have worse endothelial cell dysfunction and atherosclerotic changes in vasculature after acute respiratory infections than healthy children indicating interplay between HLA and infections on the wall of blood vessels. 75 In addition, class I HLA genes have been associated with T1D. Young age, autoantibody profiles, and higher prevalence of non-HLA FUT2 (fucosyltransferase 2) SNPs with predisposing HLA-risk genes may characterize rapid disease progression in children.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…In addition to periodontitis, recent studies have shown aMMP-8 to be associated with chronic inflammation and inflammatory diseases including obesity, rheumatoid arthritis and cardiovascular diseases (Äyräväinen et al, 2018;Lauhio et al, 2016;Tuomainen et al, 2014). Furthermore, aMMP-8 has been observed to be associated with an elevated C-reactive protein level among subjects with the diabetes risk genotype HLA-DQ2/8 (Odermarsky et al, 2018).…”
mentioning
confidence: 99%